Developing Learning Media based on AR-VR to Enhance Junior High School Students’ Understanding of Human Digestive System Materials - Ridlo, Zainur Rasyid; Bachtiar, Rayendra Wahyu; Wahyuni, Sri; Mahardika, I Ketut; Wicaksono, Iwan; Ningsih, Silvi Putri Ayu; Ulfa, Efrika Marsya; Zuniari, Nurul Iqdami (Jurnal Pendidikan MIPA, 2024)
The research aims to develop an Android-based Augmented-Virtual Reality learning medium on digestive system materials for junior high school on human digestive system materials. The study implemented an instructional design model based on ADDIE, with eight classroom meetings to assess student learning outcomes. Pretest and posttest scores were used to calculate the N-gain score, reflecting the students’ improvement in understanding the material. The study involved 40 students. The results showed a significant improvement in student performance, with an N-gain score of 0.62, indicating moderate learning gains. The practical application of the media was deemed feasible, and students reported high levels of engagement and satisfaction with the media. These findings suggest that the learning media effectively supported the students' comprehension and engagement in science, and the use of the ADDIE model provided a structured approach to assessing its impact on learning. The creation of Augmented-Virtual Reality on Assemblr edu and MilleaLab application also seems simple so that it can be easy for developers to create the desired material.       Keywords: learning media, augmented-virtual reality, assemblr edu, millealab, ADDIEDOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1297-1316